Epidemiological profile of emergency hospitalizations for mental and behavioral disorders due to alcohol use in Piauí state between the years 2017 - 2021 - Alves Neta, Marlene Rodrigues de Melo; Benvindo , Rayssa Dantas Nogueira; Barradas, Isabelle Lima; Santana, Paulo Roberto Oliveira Henrique (Seven Editora, 2023)
Although the increase in alcohol use is evident, very little is known about emergency hospitalizations, and the data collected so far show a large association between alcohol and mental and behavioral disorders. Realizing the need for information and greater social attention, this study aimed to identify the epidemiological indices of emergency hospitalizations for mental and behavioral disorders due to alcohol use in Piauí. A quantitative, retrospective, and epidemiological methodological approach was used, showing the number of emergency admissions for mental and behavioral disorders due to alcohol use. Data were collected through the SUS Department of Informatics (DATASUS), and the variables investigated were gender, age group, color/race, and place of occurrence. The information pointed out that, unlike the negative and homogenizing view of the other around a disorder and alcohol dependence, an adequate intervention is needed to change this social structure. DOI: https://doi.org/10.56238/colleinternhealthscienv1-008